IOT based Breast Cancer Monitoring using MRI images Post Neoadjuvant Therapy - Gangaiah, Madhura; Pallavi, Andhe (International Journal of Computer Sciences and Engineering, 2025)
Metastatic cancer remains a key task in medical management of the disease, since most cancer mortality rates are accredited to metastatic spread of cancer rather than the primary tumor. Despite the noteworthy improvements in the diagnosis, treatment and clinical management, prediction of prognosis, breast cancer relapse and death rates remain unacceptably high in women worldwide. Magnetic Resonance Imaging serves as an important source in detection, diagnoses and treatment monitoring of Breast Cancer. Image processing techniques like pre-processing using different filters to remove the noise content, image segmentation methods to extract the feature such as major axis length, minor axis length are applied to breast MRI images. A mobile app is developed to send the pre-processed MRI images to the doctors’ smart phone. The aim is to augment the view of the MRI images and interpret the condition of the patient as well as to enrich the overall interpretation process. The objective of the work is the analysis of MRI images which reflect the response of the neoadjuvant therapy administered at each successive stage to breast cancer patients in steps.